2018
DOI: 10.3892/mmr.2018.9098
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‑195 suppresses cell proliferation of ovarian cancer cell by regulating VEGFR2 and AKT signaling pathways

Jun Chen

Abstract: The present study aimed to investigate the functional effects of microRNA‑195 on ovarian cancer cells and the underling mechanism involved. Reverse transcription‑quantitative polymerase chain reaction was used to measure the expression of microRNA‑195 in patients with ovarian cancer. Cell proliferation and apoptosis were measured with MTT assay and flow cytometry, respectively. Caspase‑3/9 activity, vascular endothelial growth factor receptor (VEGFR)2 and phosphorylated protein kinase B (p‑AKT) protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Finally, the present study did not investigate AKT and its inhibitors on the effect of miR-195. A previous study revealed that miR-195 inhibited VEGFR2 and AKT signaling ( 12 ); therefore, further evidence regarding the under-lying molecular mechanism of miR-195 is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the present study did not investigate AKT and its inhibitors on the effect of miR-195. A previous study revealed that miR-195 inhibited VEGFR2 and AKT signaling ( 12 ); therefore, further evidence regarding the under-lying molecular mechanism of miR-195 is required.…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR was conducted to determine miR-195 expression in tissues and cells, as well as to determine CDC42 and CCND1 mRNA expression levels in OVCAR-3 cells, as previously described ( 12 ). Total RNA was isolated using TRIzol ® reagent (Invitrogen; Thermo Fisher Scientific, Inc.) at room temperature, according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…qRT-PCR was carried out to quantify the mRNA expression levels of GINS2, p53 and GADD45A in clinical specimens, mice femoral tissues and diverse osteoblasts and osteoclasts referencing the previous report (Chen, 2018). Briefly, total RNA was extracted and isolated using Trizol reagent (Invitrogen, USA) according to the manufacturer's instructions.…”
Section: Real-time Quantitative Reverse Transcription-polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%